How Congressmen Connect: Analyzing Voting and Donation Networks in the Brazilian Congress - Bursztyn, Victor S.; Nunes, Marcelo Granja; Figueiredo, Daniel R. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2016)
The goal of this work is to analyze two of the most central activities in the life of a congressman: raising funds and voting bills. We investigate the Brazilian Congress to shed light on the relationships between the donations received by congressmen elected in 2014 and their voting behaviors during the year of 2015. We merged publicly available data obtained from the Brazilian House of Representatives and the Superior Electoral Court (TSE) in order to create a tripartite network containing campaign donors, elected congressmen, and legal bills. Using this data, we create two projected networks having congressmen as nodes and links given as follows: 1) congressmen who received donations from the same donors (donation network); and 2) congressmen who voted in accordance to each other on legal bills (voting network). After characterizing these networks, we propose three fundamental questions on the behavior of congressmen that could benefit from the methods and concepts provided by Network Science. Finally, we analyze the results and compare them to general domain knowledge.